Peran Kepemimpinan Karismatik Dalam Meningkatkan Kinerja Kerja PT Sapta Sinergi Nawasena - Nurwati, Bunga Alfitria; Fauzan, Rizky Muhammad; Fitriani, Erni; Nuralim, Aji (Yayasan Cendekia Gagayunan Indonesia, 2025)
This study aims to examine the influence of charismatic leadership style on employee performance at PT Sapta Sinergi Nawasena. Utilizing a qualitative approach, data was collected through in-depth interviews with management and employees. The findings indicate that the charismatic leadership of Ms. W significantly contributes to enhancing employee motivation and productivity. Charismatic leaders can inspire their teams through a clear vision and effective communication, thus creating a positive work environment. These findings are expected to provide insights for the development of managerial strategies and leadership practices in organizations.